The Art of Feelings / Nur Shaliza Sapiai and Junaidi Awang - Sapiai, Nur Shaliza; Awang, Junaidi (Faculty of Art and Design, 2021)
The artwork of interpreting that Pandemic Covid-19 has created a diversity of tastes, feelings, emotions, psychiatry, reactions and behaviors that translateto self-expression for an educator. Everyone can enjoy happiness with what they love, so look for that happiness, happiness comes in critical moments when we love what we do every day. Happiness is able to transcend the problems of life, so everyone should enjoy the feeling of happiness despite the challenges. Tell yourself that IQ =Intelligent Quotient and academic acumen only contribute 20% to a person’s success compared to 80% coming from EQ = emotionally intelligent. Thus, emotional stability and calm are very important in dealing with daily situations.